The Influence of IT affordance and Seller attributes on Consumer Trust on Fashion Live Streaming and its impact on Purchase Intention - Wandoko, Wanda; Gunawan, Djohan; Khalishah, Siti Ruqayyah; Puspita M S S, Sola Gracia; Panggati, Ignatius Enda (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The purpose of this study is to analyse the influence of visibility, guidance shopping, seller verbal attractiveness and seller interactivity on consumer trust in fashion live streaming, and to examine the impact of this trust on consumers' purchase intentions in fashion live streaming. Design/methodology/approach: This study uses the S-O-R theory as the basis for developing the research model. The approach used is quantitative. The respondents of this study are consumers of fashion live streaming in Indonesia, with 372 respondents' data being processed using SEM PLS tools. Findings: The results of this study indicate that consumer trust in fashion live streaming significantly impacts the increase in consumers' purchase intentions. The study also shows that consumer trust in fashion live streaming is influenced by seller verbal attractiveness, seller interactivity, and visibility , guidance shopping. This research has implications for the SOR theory and affordance theory. Furthermore, it also has managerial implications. Paper type: Research paper